Rural-Urban Migration Challenges in South Africa: Case of Kwazulu-Natal (SA) - B. Nkabinde; L.M Lekhanya; N. Dorasamy (Journal of Economic and Social Development (Varaždin))
Townships in South Africa were designed and established when apartheid was at its peak. The challenge facing the democratic government in the developmental local sphere of government, is inefficient service provision, due to the continuous increase of local inhabitants, caused by an increased rate of rural-urban migration patterns. Urban planning focuses on city and town design and how the municipality delivers services to communities dwelling within these designed urban spaces. Rural-urban migration is the movement of people from rural to urban areas, with the main reason the pursuit of better opportunities to improve their socioeconomic conditions. Therefore, the pull and push factors of rural to urban migration are clearly defined and explained in order to assist the municipal administration and academia to improve urban service delivery. The study adopts a quantitative approach with the sample comprising 350 respondents, purposively selected through non-probability sampling and required to complete a 5-point Likert scale questionnaire. The researcher assisted in terms of questionnaire administration. The completed questionnaire provided the quantitative data for statistical analysis, using SPSS version 28.0. Study findings indicate that, among other factors, a strong significance exists regarding increased crime levels in urban areas as a result of rural-urban migration patterns, with suggestions that include more money needs to be prioritised from government for policing and crime in cities such as eThekwini Municipality. Since there are more informal settlements because of rural-urban migration, it is also shown as necessary to create network infrastructure in rural areas to improve communication for those working from home. To identify and explain migration to enhance service delivery at eThekwini Municipality, the study investigated the pull and push factors in migration patterns and their influence on service delivery, as well as examining the extent to which rural-urban migration can be used to deal with the current state of service delivery. In addition, the study determined the role of rural-urban migration in the overpopulation of urban areas at eThekwini Municipality, to suggest and recommend a conceptual framework that should be employed to improve the current state of service delivery in the municipality.